2021
DOI: 10.1186/s12885-021-07922-5
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib in advanced EGFR-T790M mutation-positive non-small cell lung cancer patients treated within the Special Use Medication Program in Spain: OSIREX-Spanish Lung Cancer Group

Abstract: Background AURA study reported 61% objective response rate and progression-free survival of 9.6 months with osimertinib in patients with EGFR/T790M+ non-small cell lung cancer. Due to lack of real-world data, we proposed this study to describe the experience with osimertinib in Spain. Methods Post-authorization, non-interventional Special Use Medication Program, multicenter, retrospective study in advanced EGFR/T790M+ non-small cell lung cancer. On… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(9 reference statements)
1
5
0
Order By: Relevance
“…In this context, the survival outcomes of other real-life studies varied between median 9.4 and 14.5 months of PFS, in the second-line treatment of advanced NSCLC with T790M mutation (9)(10)(11)(12)(13)(14). The Spanish Lung Cancer Group reported a median of 9.4 months PFS in 155 patients, and this was a very close to the PFS reported in the pivotal phase 3 trial (6, 10).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In this context, the survival outcomes of other real-life studies varied between median 9.4 and 14.5 months of PFS, in the second-line treatment of advanced NSCLC with T790M mutation (9)(10)(11)(12)(13)(14). The Spanish Lung Cancer Group reported a median of 9.4 months PFS in 155 patients, and this was a very close to the PFS reported in the pivotal phase 3 trial (6, 10).…”
Section: Discussionsupporting
confidence: 51%
“…In our study, ORR was higher (82%) and DCR was similar with 95%. Studies from Europe already reported lower rates with approximately 40-50% of ORR (10,12). No data was indicating that the Turkish population might be more "sensitive" to this treatment than Western population.…”
Section: Discussionmentioning
confidence: 97%
“…After the previous EGFR-TKI treatment, patients in the disease progression received the simertinib, with a disease control rate of 92.0%. Therefore, osimertinib is certified as a groundbreaking therapy drug for NSCLC by the FDA (26,27). The mechanism of osimertinib is that the acrylamide contained in osimertinib can form the covalent bonding with C797 at the edge of the ATP binding site in the catalytic domain of the EGFR gene, and then the irreversible binding occurs with the specific EGFR mutations, to solve the problem of abnormal signal transduction pathway in downstream cells caused by EGFR mutation, inhibit the excessive proliferation and mutation of tumor cells due to the EGFR mutation, and reduce the metastasis rate.…”
Section: Discussionmentioning
confidence: 99%
“…Osimertinib significantly prolonged the progression-free survival in treatment-naïve patients with EGFRm advanced NSCLC and in patients with EGFR T790M NSCLC after disease progression with prior EGFR-TKIs treatment [ 21 23 ]. Osimertinib also demonstrated superior CNS efficacy in T790M-positive NSCLC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%